(untitled) (Novateur Publications, 2024)
In the monograph are considered problems related to the clinical and epidemiological characteristics of stroke specific to arid zones. The author of the monograph puts forward his hypotheses about the clinical and epidemiological features of hemorrhagic stroke in Surkhandarya region. This monograph is intended as a practical guide for neurologists, family doctors, clinical residents, masters of neurology and children’s neurology specialties, and all specialists interested in this pathology.